A Novel Recognition Method for Low SNR DSSS Signals Based on Four‐Order Cumulant and Eigenvalue Analysis. Issue 3 (1st July 2015) - Guan, Mingxiang; Wang, Le
Abstract : At present it is very difficult to estimate the carrier frequency, spread spectrum code period and spread spectrum code pattern of Direct sequence spread spectrum (DSSS) signals with low Signal‐to‐noise ratio (SNR) accurately and simultaneously in the condition of Gaussian white noise. A novel method of estimation for carrier frequency and spread spectrum code period of DSSS signals based on four‐order cumulant and eigenvalue analysis is presented. Compared with the correlative detection in time domain, square filtering detection and Hebbian rule, the proposal method in this study can realize the estimation for the carrier frequency and period of spread spectrum code of low SNR DSSS signals with a high accuracy simultaneously. In a priori condition of the spread spectrum code period the proposal method can calculate synchronization loss time between spread spectrum code and information symbol. The proposal method this paper has a strong ability to suppress Gaussian noise.